Dynamic All Optical Slow Light Tunability by Using Nonlinear One Dimensional Coupled Cavity Waveguides - Bananej, Alireza; Zahedi, S. Morteza; Hamidi, S. M.; Hassanpour, Amir; Amiri, S. (IntechOpen, 2012)
None